(untitled) (Research, Society and Development, 2022)
The association of severe acute respiratory syndrome 2 (SARS-COV-2) with invasive pulmonary aspergillosis (API) is called CAPA. Clinical treatment protocols are not described in the world or national literature resulting in low efficacy and high mortality. The objective was to associate the manifestations of SARS-COV-2 and API, in relation to the diagnostic methods, pulmonary dysfunction and clinical outcome. The systematic literature review was based on Pubmed, with English descriptors: “aspergilosis”, “covid”, “histology”, boolean "and", with filters: human and published from 2019. 31 articles were identified and 10 were included. The diagnosis for API included research of the Aspergillus galactomannan antigen in serum or sputum, Aspergillus PCR in tracheal aspirate and culture of respiratory samples. The highlighted respiratory compromises are ground-glass opacities, nodular consolidations, bilateral interstitial pulmonary infiltrate, with death as one of the common outcome. CAPA is a co-infection process, future clinical trials are necessary to develop integrated diagnosis, to improve the clinical outcome and minimize mortality.